Antigenic Activity of Bacterial Endodontic Contents from Primary Root Canal Infection with Periapical Lesions against Macrophage in the Release of Interleukin-1 beta and Tumor Necrosis Factor alpha - Martinho, Frederico Canato [UNESP]; Maia Chiesa, Wanderson Miguel; Leite, Fabio R. M.; Cirelli, Joni Augusto [UNESP]; Gomes, Brenda P. F. A. (Elsevier B.V., 2010)
Introduction: Periradicular tissue chronic stimulation by endotoxin may cause apical periodontitis. This study investigated the microbial profile and the levels of endotoxin found in primary root canal infection with apical periodontitis, determined their antigenicity against macrophages through the levels of interleukin (IL)-1 beta and tumor necrosis factor alpha (TNF-alpha), and evaluated their relationship with clinical and radiographic findings. Methods: Samples were taken from 21 root canals with primary endodontic infection and apical periodontitis with paper points. PCR technique (16S rDNA) was used for the detection of the target bacteria. Limulus Amebocyte Lysate (LAL) was used to measure endotoxin. The amounts of IL-1 beta/TNF-alpha in macrophages supernatants were measured by enzyme-linked immunosorbent assay - Duoset-kit (ELISA). Results: Prevotella nigrescens (13/21), Porphyromonas endodontalis (6/21), and Treponema socranskii (6/21) were the most frequently detected gram-negative bacterial species. The presence of the sinus tract (2/21) was related to the detection of Filifactor alocis (p < 0.05), whereas a tooth with a radiolucent area >= 2 mm was related to the detection of Treponema denticola. A correlation was found between the number of gram-negative bacteria and the levels of IL-1 beta/TNF-alpha (p < 0.05). Increased levels of endotoxin were followed by TNF-alpha release (p < 0.05). Higher levels of IL-1 beta (p < 0.05) and endotoxin contents were related to the larger size of the radiolucent area. Conclusion: The antigenicity of the endodontic contents is not only related to the amount of endotoxin found in the root canal but also to the number of different species of gram-negative bacteria involved in the infection. Moreover, a larger size (2 mm) of the radiolucent area was related to IL-1 beta and endotoxin. (J Endod 2010;36:1467-1474)
Keywords: Antigenicity; bacteria; endodontic; endotoxin; macrophages